Lipid Profile Levels in Smokers - Gulfam Javed, Ahmed Hakeem Hafiz, Ayesha Tahir, Naila Ikram, Ali Ammar, Natasha Zahid (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The objective of this study was to record mean lipid profiles in smokers Methodology: All 200 (Two hundred) smokers were enrolled from Cardiology Department, Punjab Institute of cardiology Lahore during 2015 to 2016, the demographic profile of the patients’ was taken. Their ECG was done to ensure that they do not have any cardiac disease. After 12 hours over night fasting, blood samples were withdrawn from a cubital vein into blood tubes. The blood samples were sent to hospital laboratory for the analysis of lipid profile. Serum triglyceride (TG) level by GPO – PAP enzymatic colorimetric method, Serum total cholesterol (TC) level by CHOD – PAP enzymatic colorimetric method, Serum HDL-c level by precipitation method, Serum LDL-c level by using Friedewald’s formula, LDL-c = TC ˗ (HDL + TG/5), Serum VLDL-c level by using Friedewald’s formula VLDL-c = TG/5. Results: Of 200 cases 45%(n=90) were between 18-40 years of age while 55%(n=110) were between 41-60 years of age, mean+sd was calculated as 41.98+11.02 years, 89.5%(n=179) were male and 10.5%(n=21) were females, mean lipid profiles in smokers was calculated as 188.38+16 55 for total cholesterol, 157.33+15.93 triglycerides, 42.47+4.88 HDL, 114.44+13.43 LDL and 31.47+3.19 for VLDL. Conclusion: the smokers are at higher risk of developing dyslipidemia. Our results are encouraging for smokers to quit their habits to live a healthy life. Keywords: Smokers, lipid profile, mean